2008
DOI: 10.1088/0953-8984/20/9/095004
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-mediated ferromagnetism in p-Si(100) by sequential ion-implantation of B and Mn

Abstract: Ferromagnetic Si1−xMnx was prepared by implanting B+ and Mn+ ions in sequence into p-type Si(100) at room temperature and post-annealing at 700–900 °C. Superparamagnetic nano-sized silicide precipitates, 10–27 at.% Mn, were found near the surface of all Si1−xMnx samples. Annealing at 800 °C or below leads to the formation of a thin Si(Mn) layer, with 1.1 at.% Mn, ∼180 nm beneath the surface, giving rise to ferromagnetism with a Curie temperature above 250 K. The high-temperature ferromagnetism is attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…However, among the work published on Mn-doped Si DMS, the results are inconsistent, even controversial. Si 1Àx Mn x prepared by ionimplantation technology showed ferromagnetism with a Curie temperature ranging from 70 to 600 K [6][7][8][9][10][11][12]. It was also reported that Si 1Àx Mn x films fabricated by vacuum evaporation, magnetron sputtering or molecular beam epitaxy had been observed ferromagnetism around room temperature [13][14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…However, among the work published on Mn-doped Si DMS, the results are inconsistent, even controversial. Si 1Àx Mn x prepared by ionimplantation technology showed ferromagnetism with a Curie temperature ranging from 70 to 600 K [6][7][8][9][10][11][12]. It was also reported that Si 1Àx Mn x films fabricated by vacuum evaporation, magnetron sputtering or molecular beam epitaxy had been observed ferromagnetism around room temperature [13][14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…The effect of p-type (or n-type) doping has been simulated by employing one extra positive (or negative) charge in a 64 atom unit cell compensated by constant background potential to maintain charge neutrality. This gives a background carrier concentration of about 10 20 cm −3 , which is much higher than typical experimental concentrations of about 10 15 cm −3 (12). Reduction of background carrier concentration requires larger super cell sizes, which has not been considered in current calculations.…”
Section: Methodsmentioning
confidence: 79%
“…However, extensive experiments revealed that Mn-rich precipitates were developed and buried in a crystalline Ge matrix (Park et al, 2005, Lin et al, 2008, Verna et al, 2006, D'Orazio et al, 2002, Liu et al, 2004, Lifeng et al, 2004 in a much similar manner to that of the thin films grown by MBE (Park et al, 2001, Bougeard et al, 2006, Li et al, 2007, Demidov et al, 2006.…”
Section: Overview Of the Mn Doped Gementioning
confidence: 92%
“…In particular, the hole mediated effect discovered in Mn x Ge 1-x DMS opens up tremendous possibilities to realize spintronic devices with advantages in reducing power dissipation and increasing new functionalities, leading to perhaps normally off computers. To date, there are many reports on the Mn x Ge 1-x growth and characterizations by molecular beam epitaxy (MBE) (Park et al, 2002, Li et al, 2005, Jamet et al, 2006, Tsui et al, 2003, Ahlers et al, 2006a, Ahlers et al, 2006b, Bougeard et al, 2006, Devillers et al, 2007, Li et al, 2007, Park et al, 2001, Wang et al, 2008a, Pinto et al, 2005b, ion implantation (Park et al, 2005, Lin et al, 2008, Verna et al, 2006, D'Orazio et al, 2002, Liu et al, 2004, Lifeng et al, 2004, and bulk crystal growth (Cho et al, 2002, Biegger et al, 2007. We can divide them here, for an easier orientation, into two groups: those that cover fundermantal studies of phase formation, ferromagnetism, and transport properties (Park et al, 2002, Li et al, 2005, Majumdar et al, 2009a, Wang et al, 2008a, Gunnella et al, 2005, Liu et al, 2006, Jamet et al, 2006, Li et al, 2006b, Zhu et al, 2004, Miyoshi et al, 1999, Li et al, 2006a, Zeng et al, 2006, Cho et al, 2002, Liu and Reinke, 2008, Gambardella et al, 2007…”
Section: Overview Of the Mn Doped Gementioning
confidence: 99%
See 1 more Smart Citation